Mountain goats are my weakness : and other tales of life in the Northwest - Kershner, Jim, 1953- (New Media Ventures, 2004)
When future archaeologists dig this volume from the rubble heap of our lost civilization, they will conclude, correctly, that the average American (1997-2004) was a beer-loving, fishing-obsessed owner of pet Sea Monkeys; a man constantly besieged by amorous mountain goats, psychotic robins, the occasional comatose moose and his own evil cell phone. Or maybe not. Maybe they will regard this collection of columns the way discriminating readers regard it today: As a psychiatric case study of a disturbed Northwest family and their various obsessions, including, but not limited to, drunken-bird watching, turducken eating, highway construction spotting, password forgetting and secrets-of-the-universe pondering. Here are just a few of the issues on the table: Middle-aged men and their penchant for beer bellies, Hawaiian shirts and "overbite dancing." Women and their penchant for indiscriminate nurturing. Cell phones, and how they want to kill us. Money, and how it no longer exists in America. Marriage, and why it is no longer a sacrilege to marry your best friend. Driving, and why it should never be done with relatives. Memory-loss, and how it sometimes strikes in the shower. The mountains, and the dangers of hiking with Ranger Rick. Trout streams, and why we fall down in them. Food, and why "spotted dick" is called "spotted dick." Beer, and why it is the ultimate Lenten sacrifice. Moose attacks, and how to avoid them. Germ warfare, and how to enjoy it. Obscene language, and how to kick some donkey. Saying "you're welcome," and why it's so hard to do. Sports injuries, and how to pull both of your groins. The war between cats and dogs, and why humans are so often caught in the crossfire. The universe, and the difficulty we have in grasping it. Children, and the difficulty we have in releasing our grasp.